2022
DOI: 10.3390/signals3020022
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Study on Ensemble of Segmentation Approaches

Abstract: Recognizing objects in images requires complex skills that involve knowledge about the context and the ability to identify the borders of the objects. In computer vision, this task is called semantic segmentation and it pertains to the classification of each pixel in an image. The task is of main importance in many real-life scenarios: in autonomous vehicles, it allows the identification of objects surrounding the vehicle; in medical diagnosis, it improves the ability of early detecting of dangerous pathologie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 61 publications
0
35
0
Order By: Relevance
“…In this section, we report the results about the empirical analysis performed for the hand segmentation task. We also provide an ablation study that shows the importance of adopting an ensemble based on DeepLabV3+; this ablation study, for the skin segmentation, have been already reported in [60].…”
Section: Hand Segmentationmentioning
confidence: 90%
See 3 more Smart Citations
“…In this section, we report the results about the empirical analysis performed for the hand segmentation task. We also provide an ablation study that shows the importance of adopting an ensemble based on DeepLabV3+; this ablation study, for the skin segmentation, have been already reported in [60].…”
Section: Hand Segmentationmentioning
confidence: 90%
“…• In [1] and [60] several deep learning segmentation approaches are compared, SegNet, U-Net, DeepLabv3+, HarD-NetMSEG (Harmonic Densely Connected Network) 1 [61] and Polyp-PVT [62] a deep learning segmentation model based on a transformer encoder, i.e. PVT (Pyramid Vision Transformer) 2 .…”
Section: Skin Detection Approachesmentioning
confidence: 99%
See 2 more Smart Citations
“…DA2 is a more articulated procedure. We refer to [22] for an exhaustive description of the two approaches. Some artificial images (DA2 approach) contain only background pixels, to discard them we simply delete all the images where there are less than 10 pixels that belong to the foreground class.…”
Section: Data Augmentationmentioning
confidence: 99%